2020
DOI: 10.1155/2020/3024793
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrasonographic Features of Shoulder Pain Patients in a Tertiary Hospital in South China

Abstract: Background and Objective. Musculoskeletal ultrasound imaging can play a role as an accurate tool in offering an accurate diagnosis of shoulder pain. However, it is still not commonly used in mainland China. The aim of this study was to explore the epidemiology and ultrasound imaging characteristics of shoulder pain patients in south China and hoping to use these data in the future development of artificial intelligent ultrasound interpretation of shoulder pathology. Methods. Patients with shoulder pain were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The most common pathologies are rotator cuff pathologies followed by ACJ arthritis, LBT tendinitis, and subacromial–subdeltoid (SA-SD) bursitis. A study done in Kenya (D Mang'Oka etal) and a similar observation in another study (Li Jiang et-al) found subacromial disorders including rotator cuff tendinosis, calcific tendinosis, rotator cuff tear, and subdeltoid bursitis accounting for the majority of shoulder pathologies ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The most common pathologies are rotator cuff pathologies followed by ACJ arthritis, LBT tendinitis, and subacromial–subdeltoid (SA-SD) bursitis. A study done in Kenya (D Mang'Oka etal) and a similar observation in another study (Li Jiang et-al) found subacromial disorders including rotator cuff tendinosis, calcific tendinosis, rotator cuff tear, and subdeltoid bursitis accounting for the majority of shoulder pathologies ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 69%
“…In our study, we also observed that middle age and old age groups accounted for over 3/4 th of the cases. D.Mango etal and Li Jiang etal also showed increased prevalence with age ( 4 , 5 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the case of studies in which the study group consisted of patients with hemiplegia due to stroke, ultrasonographic assessment of shoulder structures allows for an analysis of shoulder pain with paresis, and redirection to another specialist or modification of the treatment at the same time [30,34]. The use of RUSI in the field of musculoskeletal disorders allows for an analysis of shoulder diseases in terms of morphological damage to structures and functions, enabling the correct clinical decision to be made [13,14,17,22,23,36,39,54]. Control of integrity of the re- Results not yet published doi.org/10.56984/8ZG1A6k5q constructed tendons and of trophic functions of the rotator cuff muscles allows for a safe patient guidance during recuperation period [54].…”
Section: Discussionmentioning
confidence: 99%
“…An age of 40 years or older was most strongly related to rotator cuff disease. In another study (9), a total of 380 shoulders were assessed using musculoskeletal US imaging. Other researchers (6) reported in their study that US was effective imaging modality for detection of Rotator cuff tears with an US agreement to MRI was 90% for full thickness tears and 85.5% for partialthickness tears.…”
Section: Image Interpretationmentioning
confidence: 99%